Providing care in underresourced areas: contribution of the physician assistant/associate workforce - Mirela Bruza-Augatis; Bettie Coplan; Kasey Puckett; Andrzej Kozikowski (BMC Health Services Research, 2024)
Abstract Background Prior studies suggest that physician assistants/associates (PAs) are more likely than physicians to work in underresourced areas. However, data characterizing the current PA workforce in health professional shortage areas (HPSAs) and medically underserved areas (MUAs) are lacking. Methods We analyzed the 2022 cross-sectional dataset from a comprehensive national database to examine the demographic and practice characteristics of PAs working in HPSAs/MUAs compared to those in other settings. Analyses included descriptive and bivariate statistics, along with multivariate logistic regression. Results Nearly 23% of PAs reported practicing in HPSAs/MUAs. Among PAs in HPSAs/MUAs, over a third (34.6%) work in primary care settings, 33.3% identify as men, 15.6% reside in rural/isolated areas, and 14.0% are from an underrepresented in medicine (URiM) background. Factors associated with higher odds of practicing in a HPSA/MUA included residing in rural/isolated settings, URiM background, and speaking a language other than English with patients. Conclusions As the PA profession grows, knowledge of these attributes may help inform efforts to expand PA workforce contributions to address provider shortages.